Gas‒phase reactions of NO+ with Glu and γ‒Glu–Met. Issue 4 (2000) - Wincel Wincel, H. H.; Fokkens Fokkens, R. H. R. H.; Nibbering Nibbering, N. M. M. N. M. M.
Abstract : The reactivity of the nitrosonium ion, NO +, with the amino acid Glu and the dipeptide γ‒Glu–Met in the gas phase has been investigated using the combination of chemical ionisation mass spectrometry and MS/MS. It is shown that NO + reacts efficiently with both Glu and Glu–Met leading to the formation of the nitroso‒group containing ions at m/z 159 and 288. The formation of m/z 159, (GluNO‒18) +, is rationalized by a mechanism involving an electrophilic attack of NO + upon the carbonyl oxygen atom of one of the carboxylic groups of Glu and the N‒terminal carboxylic group of Glu–Met leading to the neutral losses of H2 O and Met, respectively. The unimolecular decompositions of the metastable and collisionally activated m/z 159 ions lead primarily to the elimination of the neutral species HNO (major) and the (Glu‒18) residue (minor). The formation of the m/z 288 ions can be described by a mechanistic scheme which involves the ion‒molecule interaction of m/z 159 with Glu and Glu–Met and subsequent losses of H2 O and Met, respectively. Unimolecular and collisionally activated dissociations of m/z 288 suggest the formation of the proton‒bridged ion‒neutral complex [(GluNO‒18)···H + ···(Glu‒18)].